HUMAN RESOURCE MANAGEMENT IN EDUCATIONAL MANAGEMENT: CASE STUDY AT SULTAN AGUNG VOCATIONAL SCHOOL - muhammad fahraz fahlefi (JURNAL ASIK, 2025)
This research aims to examine the implementation of Human Resource Management (HRM) in educational management at Sultan Agung Vocational School, focusing on the challenges, strategies, and effectiveness of HR practices in improving the quality of education. Human resources in vocational schools play a crucial role in preparing students with skills that are directly relevant to the labor market. However, various issues related to HRM, such as the qualification of teaching staff, professional development, and organizational coordination, have hindered the optimal development of students' competencies. This qualitative study utilizes in-depth interviews and document analysis as primary data collection methods to explore HRM practices at Sultan Agung Vocational School. The findings indicate several key challenges, including a shortage of qualified instructors in specialized fields, limited opportunities for staff training and development, and a lack of structured evaluation and career development systems for educators. Furthermore, weak coordination within the school’s administrative structure has resulted in inefficiencies in managing staff and aligning educational objectives with industry needs. Based on these findings, the study offers recommendations for improving HRM practices, such as enhancing teacher qualification programs, establishing continuous professional development initiatives, and implementing comprehensive performance evaluation systems. This research contributes to the understanding of HRM in educational settings, particularly in vocational schools, and provides insights for enhancing HR practices to improve educational outcomes and student employability.